Mothering Performance Maternal Action - Šimić, Lena; Underwood-Lee, Emily (Routledge Advances in Theatre & Performance Studies, 2023)
Mothering Performance is a combination of scholarly essays and creative responses which focus on maternal performance and its applications from a variety of interdisciplinary perspectives. This collection extends the concept and action of 'performance' and connects it to the idea of 'mothering' as activity. Mothering, as a form of doing, is a site of never-ending political and personal production; it is situated in a specific place, and it is undertaken by specific bodies, marked by experience and context. The authors explore the potential of a maternal sensibility to move us towards maternal action that is explicitly political, ethical, and in relation to our others. Presented in three sections, Exchange, Practice, and Solidarity, the book includes international contributions from scholars and artists covering topics including ecology, migration, race, class, history, incarceration, mental health, domestic violence, intergenerational exchange, childcare, and peacebuilding. The collection gathers diverse maternal performance practices and methodologies which address aesthetics, dramaturgy, activism, pregnancy, everyday mothering, and menopause. The book is a great read for artists, maternal health and care professionals, and scholars. Researchers with an interest in feminist performance and motherhood, within the disciplines of performance studies, maternal studies, and women's studies, and all those who wish to gain a deeper understanding of maternal experience, will find much of interest. The Open Access version of this book, available at www.taylorfrancis.com, has been made available under a Creative Commons Attribution-Non Commercial-No Derivatives 4.0 license. Funded by University of South Wales